Fabrication of Anti-Termite Particle Boards Made from Bintaro (Cerbera Manghas): Analysis of Physical and Mechanical Properties (Universitas Muhammadiyah Yogyakarta, 2023)
Termites are commonly seen as a nuisance due to their capacity to cause harm to wooden objects. The occurrence of termite infestations on furniture has led to a rise in financial damages attributed to such attacks. Hence, it is of utmost need to seek alternative raw materials that exhibit resistance to termite-induced deterioration, thereby fulfilling the requirement for substituting particle board. The present study has successfully demonstrated the fabrication of particle board by including bintaro fruit seed filler and urea formaldehyde matrix. The primary objective of this research endeavor was to explore an alternate approach to standard particle board production, specifically focusing on the development of anti-termite qualities. The filler fraction to matrix fraction comparison exhibits variations of 50:50, 60:40, 70:30, and 80:20. The particle board production process employed in this study utilizes a cold pressing method, wherein a pressure of 15 MPa is applied for a duration of 120 minutes. The board particles that have been acquired are subjected to testing in order to ascertain their physical characteristics, such as density and water content. The experiment was conducted in compliance with the SNI Standard 03-2105-2006. The flexural strength of particle board was evaluated in accordance with the standard SNI 03-2105-2006. An assessment was conducted to evaluate the susceptibility of particle board to termite infestation, in accordance with the guidelines outlined in the SNI 01-7207-2006 standards. The density and moisture content testing findings conducted on particle board match with the specifications outlined in the SNI 03-2105-2006 standard. The experimental outcomes evaluating the susceptibility of board particles to termite infestations have effectively fulfilled the requirements outlined in the SNI 01-7207-2006 standards.